The Molecular Aspect of Natural Secondary Metabolite Products in Health and Disease - Toshio Morikawa (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. [Natural secondary metabolite products, which are isolated from plants, animals, microorganisms, etc., are classified as polyketides, isoprenoids, steroids, aromatics, alkaloids, etc. Their chemical diversity and variety of biological activities have attracted the attention of chemists, biochemists, biologists, etc. This Special Issue on "The Molecular Aspect of Natural Secondary Metabolite Products in Health and Disease" is intended to offer biological active natural products as candidates and/or leads for pharmaceuticals, dietary supplements, functional foods, cosmetics, food additives, etc. The research fields of this Special Issue include natural products chemistry, phytochemistry, pharmacognosy, food chemistry, bioorganic synthetic chemistry, molecular pharmacology, molecular nutritional sciences, and other related research fields of bioactive natural secondary metabolite products. Original research and review articles on all topics in these research fields are invited. I look forward to receiving many submissions from outstanding expert on these research fields.